Deep NIR Surveys in the Galactic Plane: A General Overview and the Study of Scutum’s Spiral Arm - Amôres, E. B.; Levenhagen, R. S. (Frontiers in Astronomy and Space Sciences, 2021)
Despite the impressive advances in Galactic structure studies thanks to the large astronomical surveys, there remain several open questions. Although at low distances, optical surveys can bring us important information, the potential of NIR surveys, combined with the optical data, should be considered. In the present work, we explore the stellar distribution through the most recent NIR surveys towards low latitudes ($|b|$ $<$ 2$^{°}$ for 20$^{°}$ $\le \ell \le$ 346$^{°}$) in the Galactic disk, such as 2MASS (entire plane), UKIDSS (20$^{°}$ $\le \ell \le$ 231$^{°}$) and VVV-PSF data (295$^{°}$ $\le \ell \le$ 346$^{°}$), avoiding directions towards the Galactic bar and bulge. Our final compilation contains nearly 140 million stars. We used this sample to perform total star counts at different longitudes, obtaining longitudinal profiles that are compared with those of other authors. For some directions we obtained the stellar density as a function of distance, to investigate the stellar distribution in the Galactic disk. As an example, the variation of the counts towards the Scutum arm tangential direction reveals the stellar content of two spiral arms. e.g., Sagittarius and Scutum. These are preliminary results of a study that will cover a large extension of the Galactic disk.